Evaluation of Anxiety and Depression among a Sample of Hypothyroidism-Treated Iraqi Patients - Nada Hamid Rasheed; Basma Zuheir Al-Metwali; Mohamed Sadoon Mohsen Al Shamaa (College of Pharmacy University of Baghdad, 2023)
Background: Hypothyroidism is the most prevalent thyroid disorders worldwide.  Hypothyroidism manifestations are wide spectrum, affecting various systems in human body including the nervous system. Hypothyroidism can cause neuropsychiatric symptoms such as anxiety, depression and diminishing in attention, memory and executive function. Aim: to investigate the level of anxiety and depression in patients with hypothyroidism receiving levothyroxine treatment. Method: a cross-sectional study was conducted at Baghdad Center for Nuclear Medicine and Radiation Therapy from March to June 2022. The study population included patients of both genders, aged 18-65 years, diagnosed with hypothyroidism, were receiving levothyroxine treatment and have achieved euthyroid state for at least 2 months prior to their enrolment in the study. Based on levothyroxine dose, the enrolled patients were divided into two groups: low dose group < 1.7 µg/kg/day and high dose group ≥ 1.7 µg/kg. Hospital Anxiety and Depression Scale (HADS) was used for the evaluation of anxiety and depression. Result: The mean age of the participants was 40.35 ± 9.5 years with mean body mass index of 30.61 ± 5.72 kg/m2. The mean scores of anxiety and depression for the total sample are 8.72 ±3.46 and 7.80 ±2.83; respectively, there was statistically non-significant difference for anxiety and depression scores between the low dose group and the high dose group. Conclusion: the presence of anxiety and depression symptoms although the patients were in euthyroid state. However, socio-demographic and clinical characteristics did not significantly influence the scores of anxiety and depression.